Análisis de las narrativas digitales en Tiktok, un recurso comunicacional explotado por los psicólogos de habla hispana - Álvarez Chávez, Angie Massiel (2023)
Social networks have allowed people to stay connected without limitation of distance or time, leading us to become a digitized society. Tiktok has become a phenomenon where the vast majority of people seek to be present, either to publicize their skills and talents or to present their products or services, leading people to greater knowledge on a specific topic. This research is based on the social network Tiktok due to its current boom, analyzing within it the content made by Spanish-speaking psychologists, to understand what are the main characteristics of the digital narratives they publish and to examine the formats that are most used. often as a communication tool to connect with your potential patients and followers. For this purpose, a mixed approach was used using a methodological triangulation, in which qualitative and quantitative approaches were used, using interviews and content analysis that allowed collecting relevant and measurable information on the formats that psychologists prefer. Through the analytical method, the aim is to observe all the aforementioned variables, to know their choices, the reactions of their followers and the choice of content and format they publish. The most significant results lead us to understand that psychologists mainly choose to present themselves in the first person, through videos or narrated images to generate a real and close connection with the people who look at them, taking into account that in psychotherapy the voice has the capacity to heal through the word.